Advancing Islamic Education Through Total Quality Management: Insights from Tahfiz Qur'an Practices - Taufikin, Taufikin; zamroni, zamroni; Nurhayati, Sri (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study addresses the lack of a standard framework for implementing the Quran memorization program and examines how a quality management approach can enhance learning outcomes in Islamic education. This study aims to analyze the implementation of Total Quality Management (TQM) in improving the effectiveness of the Quran memorization program in Islamic boarding schools. This study employs a qualitative approach, utilizing a case study design, where data are collected through document analysis, structured observations, and in-depth interviews with teachers, administrators, and parents. Thematic analysis identified three main areas of TQM implementation in learning practices: personalized memorization strategies, periodic evaluation, and collaborative engagement between stakeholders. The results showed that memorization methods that are tailored to students’ learning preferences can improve motivation and retention. Continuous evaluation and collaboration between teachers help create more responsive learning. The use of simple progress tracking tools also supports curriculum monitoring and improvement. These findings suggest that implementing basic TQM principles in the Quran memorization program can improve instructional consistency and learning outcomes, even in Islamic institutions with limited resources. This study presents a practical model for integrating quality management in religious-based education, offering opportunities for further empirical research.